Analisis Struktur Data Informatika Pada Platform Online Travel Agent - Saipullah, Fasya; Simatupang, Reza Riansyah; Batubara, Ihsan Abdul Hafiz; Wijaya, Abdul Rahman; Gunawan, Indra (Journal of Computer Science and Information System(JCoInS), 2025)
This study aims to determine how to analyze informatics data structures on online travel agent platforms. This study uses a qualitative descriptive approach with a literature study method that aims to explore and analyze the use and application of data structures in online travel agent (OTA) platforms. The results of the study indicate that data processing efficiency, user information security, and data search optimization on the Online Travel Agent (OTA) platform are highly dependent on the use of appropriate data structures. Data structures such as hash tables, graphs, queues, and linked lists have been shown to increase access speed, manage transactions efficiently, and strengthen security systems. In addition, the use of big data allows OTAs to analyze user behavior, predict ticket prices, and compile alternative flight routes. With structured and secure data management, the OTA platform is not only able to provide responsive services, but also maintain user trust and comfort.